Yza Fava de Oliveira : uma intelectual mediadora à frente do Departamento de História da Universidade de Santos (1978-1994) - Alves, Edson Rossetti (2017)
This present study investigates the journey of the history¿s course, in the period of teacher Yza Fava de Oliveira¿s management. This research gives highlight to the instruments that the course organized to reach its development goals on historic research, patrimony defense and construction of the Baixada Santista¿s knowledge. Among others, Documentation Center, Folk Studies Center, Historical Study Center, Archaeological Research Institute, History Week. Using documentary research served of the main collections of the Department and the support organs. The interviews made with the coordinator were equally important. That was important because it completed some doubts found in the documentary sources and motivated other ways of looking at reality. Besides the written documentation, the iconographic collections of the teacher and Department were important. It was also possible to have a preliminary view of the Course, under the school practices.